2005
DOI: 10.1248/cpb.53.625
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of Nitric Oxide Production from the Rhizomes of Alpinia galanga: Structures of New 8-9' Linked Neolignans and Sesquineolignan

Abstract: The 80% aqueous acetone extract from the rhizomes of Alpinia galanga showed nitric oxide (NO) production inhibitory activities in mouse peritoneal macrophages. From the aqueous acetone extract, three new 8-9 linked neolignans, galanganal, galanganols A and B, and a sesquineolignan, galanganol C, were isolated together with nine known phenylpropanoids and p-hydroxybenzaldehyde. The structures of new neolignans were determined on the basis of physicochemical and chemical evidence. In addition, the inhibitory eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 44 publications
(47 reference statements)
2
70
0
1
Order By: Relevance
“…As a part of our studies to characterize the bioactive components of natural medicines, we have investigated various NO production inhibitors, i.e., higher unsaturated fatty acids, 27) polyacetylenes, [28][29][30] coumarins, 28,30,31) flavonoids, 29,32) stilbenes, 33,34) lignans, [35][36][37] sesquiterpenes, [38][39][40][41][42][43][44][45] diterpenes, 46,47) triterpenes, [48][49][50][51] diarylheptanoids, [52][53][54] cyclic peptides, 50) alkaloids, 55,56) and phenylpropanoids. 5,6,37) Continuing of these studies, the effects of the principal constituents from E. expansa on NO production from LPS-activated macrophages were examined, and the results were summarized in Table 2. Among them, two isoflavones, clycosin (8, IC 50 ϭ13 mM) and erythrinin B (14, 18 mM), and two rotenoids, deguelin (28, 26 mM) and rotenone (30, 27 mM), were found to show inhibitory activity, whose activities were nearly equivalent to that of caffeic acid phenetyl ester (CAPE), an inhibitor of nuclear factor-kB activation (IC 50 ϭ15 mM).…”
Section: Inhibitory Effects On No Production In Lps-activated Mouse Pmentioning
confidence: 99%
“…As a part of our studies to characterize the bioactive components of natural medicines, we have investigated various NO production inhibitors, i.e., higher unsaturated fatty acids, 27) polyacetylenes, [28][29][30] coumarins, 28,30,31) flavonoids, 29,32) stilbenes, 33,34) lignans, [35][36][37] sesquiterpenes, [38][39][40][41][42][43][44][45] diterpenes, 46,47) triterpenes, [48][49][50][51] diarylheptanoids, [52][53][54] cyclic peptides, 50) alkaloids, 55,56) and phenylpropanoids. 5,6,37) Continuing of these studies, the effects of the principal constituents from E. expansa on NO production from LPS-activated macrophages were examined, and the results were summarized in Table 2. Among them, two isoflavones, clycosin (8, IC 50 ϭ13 mM) and erythrinin B (14, 18 mM), and two rotenoids, deguelin (28, 26 mM) and rotenone (30, 27 mM), were found to show inhibitory activity, whose activities were nearly equivalent to that of caffeic acid phenetyl ester (CAPE), an inhibitor of nuclear factor-kB activation (IC 50 ϭ15 mM).…”
Section: Inhibitory Effects On No Production In Lps-activated Mouse Pmentioning
confidence: 99%
“…It has been reported that 1′-ACA possesses various biological activities, such as antitumor (Itokawa et al, 1987;Kondo et al, 1993;Moffatt et al, 2000;Zheng et al, 2002;Ito et al, 2005;Azuma et al, 2006;Campbell et al, 2007), anti-inflammation (Nakamura et al, 1998;Morikawa et al, 2005), antifungal (Janssen & Scheffer, 1985), antiviral (Ye & Li, 2006), antioxidative (Kubota et al, 2001), and xanthine oxidase inhibitory activity (Noro et al, 1988). Although it has been reported that the ethanol extract of A. galanga exhibits antibacterial activity against S. aureus (Oonmetta-aree et al, 2006), the antibacterial activity of 1′-ACA has not yet been reported.…”
Section: Resultsmentioning
confidence: 99%
“…and were screened for nitric oxide production inhibitory action. [6] A. galanga is used to treat dyspepsia, fevers, urinary incontinence, halitosis, and to reduce hoarseness in throat infections. [7] It is also used as a carminative and is useful in respiratory troubles.…”
Section: In-vitro T-cell Proliferation Assaymentioning
confidence: 99%